Decoding clinical diversity in monogenic TGFBR1 and TGFBR2 mutations: insights into the interplay of molecular mechanisms and hypomorphicity - Abu-Sailik, Fadia; Gariballa, Nesrin; Ali, Bassam R. (Frontiers in Cell and Developmental Biology, 2025)
Several autosomal-dominant monogenic disorders have been conclusively associated with mutations in TGFBR1 and TGFBR2, key receptors of the Transforming Growth Factor-β (TGFβ) signaling pathway. Although these disorders share a common cardiovascular connective tissue manifestation, different mutations present with strikingly distinctive clinical presentations leading to distinct disorders, including Loeys-Dietz syndrome Marfan syndrome type 2 (MFS2), and Thoracic Aortic Aneurysms and Dissections (TAAD). In addition, some mutations lead to Shprintzen-Goldberg syndrome which is characterized by skeletal deformities and intellectual disabilities in addition to the cardiovascular involvement, or vascular Ehlers-Danlos Syndrome (vEDS) that is associated with spontaneous rupture of the main arteries and internal organs. Furthermore, Multiple Self-healing Squamous Epithelioma (MSSE), a rare familial skin cancer, is linked to mutations in these genes. This significant phenotypic variability observed in these disorders could be attributed to various factors, ranging from the nature of the mutation including its location within the protein, the variable functional impact of the mutations (hypomorphicity), the level of disruption to the intricate interactions between signaling pathways, and the influence of modifier genes or environmental factors. In addition to haploinsufficiency, the impairment of TGFβ signaling could be exacerbated in other scenarios, such as the dominant-negative effects, in which a mutant allele disrupts the normal activity of the wild-type protein by forming non-functional receptor oligomers, hindering their trafficking. This review sheds light on these hereditary disorders, highlighting the broad spectrum of their clinical presentations associated with mutations in the same gene, their pathophysiology, and underlying molecular mechanisms. Most crucially, it underscores the critical gaps in our current understanding while proposing compelling directions for future research. This review also emphasizes the pressing need to unravel the complex genotype-phenotype correlations, which could pave the way for more precise diagnostic and therapeutic strategies.